A web-based tool for the sizing of grid-connected photovoltaic (PV) systems in Ecuador (Latin-American Journal of Computing, 2025)
The transition to cleaner and more sustainable energy sources involves the use of solar photovoltaic energy. This energy source has the potential to re-duce greenhouse gas emissions and dependence on fossil fuels. The research project focused on the development of a web-based tool for sizing photovoltaic systems in Ecuador. This tool considers several factors, including technical, theoretical, economic and environmental aspects. The tool allows sizing based on electricity consumption and power requirements. Further-more, the tool provides technical information, CO2 reduction data and eco-nomic perspectives based on the operation of the electricity system in Ecuador. The comparative validation with installed systems and similar web tools demonstrated the reliability and robustness of the developed tool.